ANALISIS YURIDIS KEDUDUKAN NARAPIDANA SEBAGAI JUSTICE COLLABORATOR - Sugiri, Bambang; Aprilianda, Nurini; Hartadi, Hanif (Jurnal Hukum & Pembangunan, 2021)
This article aims to examine the inmates position as a justice collaborator in the disclosure of organized crime that can assist law enforcement officers. This is againstthe backdrop of crown witnesses who are often used in proving criminal cases but are judged to be in violation of human rights. The difficulty of disclosure of organized crime is that the perpetrators involved in organized crime are bound by the oath of silence (omerta). Information from inmates related to crime networks he has committed, facilitates the disclosure of organized crime by law enforcement officers. This paper is based on the results of legal research with a statutory approach, conceptual approachand comparative approach. The results showed that inmates as justice collaborators have a role that can be utilized by law enforcement officials in uncovering organized crime as well as as a form of correcting the wrongdoing of the inmates themselvesas in the purpose of funding, so that inmates can be accepted back into society.